Physicochemical characterization and phase I study of CMAB008, an infliximab biosimilar produced by a different expression system - An, Qing (Drug Des Devel Ther, 2019)
BACKGROUND: Infliximab (Remicade), a chimeric monoclonal antibody against human TNFα, will inevitably face competition from biosimilar products, because of its effectiveness in autoimmune diseases and rapidly increasing market demand. According to guidelines for biosimilar development, the “biosimilar-expression system” may differ from that of the innovator, but more appropriate studies should be carried out to demonstrate the comparability between biosimilar and innovator. CMAB008 is an infliximab biosimilar candidate developed by the State Key Laboratory of Antibody Medicine and Targeted Therapy of China. Infliximab was expressed in SP2/0 cells, while CMAB008 was produced in a CHO-expression system. METHODS: In this study, infliximab and CMAB008 were compared on physicochemical and biological characterizations, including protein content, activity, physiochemical integrity, impurities, additives, and immunogenicity. RESULTS: The results showed that they were highly similar and comparable, except some differences in glycosylation. As glycosylation profiles can influence immunogenicity and occurrence of allergy or other adverse reactions of antibody therapeutics, primary tolerability and pharmacokinetics of CMAB008 were evaluated. In the phase I clinical trial, plasma concentration of CMAB008 and antidrug antibodies were also measured using ELISA and bridging ELISA, respectively. CMAB008 exhibited favorable clinical tolerability, no adverse events in the 3 mg/kg single-dose group (recommended therapeutic dosage), and no serious adverse events in the multiple-dose group. Also, no injection-site reactions were observed in the experiment. CONCLUSION: In summary, CMAB008 might have the potential to be an effective drug compared with infliximab.